1979
DOI: 10.1111/j.1751-1097.1979.tb09267.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions in Visual Pigments. The Hydrogen Bond in Vislon

Abstract: Abstract— Model studies including quantum chemical calculations and the measurement of infrared and ultraviolet spectra are presented as contributions to the elucidation of the nature of the photochemical step of vision. The importance of the hydrogen bond in which the protonated nitrogen of the retinal Schiff base is involved is stressed as well as that of the perturbation of the β‐ionone ring by negative groups. It is suggested that by combining these two perturbations the low excitation energy of rhodopsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

1980
1980
1995
1995

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 55 publications
0
38
1
Order By: Relevance
“…It is, therefore, a process which is typical for the transition from the stable species rhodopsin or isorhodopsin to their first photoproduct, bathorhodopsin. The modification of carboxylic groups may play a role in point-charge models of the chromophore in rhodopsin [6,32].…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, a process which is typical for the transition from the stable species rhodopsin or isorhodopsin to their first photoproduct, bathorhodopsin. The modification of carboxylic groups may play a role in point-charge models of the chromophore in rhodopsin [6,32].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that there must be a counter-ion at the Schiff base nitrogen has been recognized by Schaffer (124,125). If the equilibrium is 100% in favor of the C=Ni-H form one can say that the Schiff base is entirely protonated.…”
Section: Protonationmentioning
confidence: 99%
“…125. It is readily demonstrated that if the counter-ion was an aliphatic anline it would take the proton from the Schiff base; if it contains another C=N, like pyridine or the imidazole ring of histidine, for example.…”
Section: Protonation and Hydrogen Bondingmentioning
confidence: 99%
See 2 more Smart Citations